INTERNET-BASEDLEARNING APPROACH FOR ENGLISH LANGUAGEACQUISITION - Agarwal, Kumar M; Novickis, L (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article explores teachers’ and students’ benefits of using Internet-based Language Learning(IBLL) which includes teaching the English Language. This paper reports on the advantages and disadvantages of using internet resources and computers to learn and teach the English language. Until quite recently, Internet-based Language Learning (IBLL) was a topic of relevance mostly to those with a special interest in that area. Recently, though, the internet has become so widespread in educational institutions and homes and its uses have expanded so dramatically that the majority of the English language teachers have started the implications of the Internet for language learning. This article provides brief overview of how internet resources can be used for language teaching. It focuses not on a technical description of software, but rather on the pedagogical questions that teachers should consider in using internet resources.